ORGANIZATION OF TRAINING IN INTERNET BASED ON WEBINARІ (Journal of Information Technologies in Education (ITE), 2010)
Webinar is used for organizing the training in the Internet. In connection software DimDim has been chosen for doing the webinar that may be integrated to learning management system Moodle. Internet school has been created that is using for distant training based on webinars and exchanging of experience of e-commerce specialists.
Keywords: distance learning; webinars